EVALUATION OF CHINA’S HELP TO VIETNAM IN THE RESISTANCE WAR AGAINST THE UNITED STATES (1954–1975) - Phạm Duc Tho; Nguyen The Ha (Romanian Journal of Historical Studies, 2024)
The victory of the Vietnamese resistance war against the United States, which saved the country, was the result of a combination of subjective and objective factors, both domestic and international, as well as people and periods. Nearly 50 years after the successful end of the resistance war against the United States to save the country, we look back and see more clearly, fully, and thoroughly the reasons for the Vietnamese people’s magnificent victory. One of them was the significant help from friends across five continents, from socialist bloc nations in general, and especially the great and effective help from China in particular. The anti-American war in Vietnam from 1954 to 1975 had a considerable influence on the strategic interests and relationships of the main powers, China, the United States, and the Soviet Union, as well as shaping the direction of the globe in the latter half of the 20th century. In this article, the author presents an outline of the aid that China gave to Vietnam throughout the country’s resistance war against the United States (1954–1975).